Intensive Exercise Training Improves Cardiac Electrical Stability in Myocardial‐Infarcted Rats. Issue 7 (21st July 2017) - Dor‐Haim, Horesh; Lotan, Chaim; Horowitz, Michal; Swissa, Moshe
Abstract : Background: Moderate exercise training has been shown to decrease sudden cardiac death post myocardial infarction. However, the effects of intensive exercise are still controversial. Methods and Results: Fourteen myocardial‐infarcted rats were divided into sedentary (n=8) and intensive training groups (n=6) and 18 sham control rats to sedentary (n=10) and intensive training groups (n=8). Heart rate variability was obtained at weeks 1 and 8. The inducibility of ventricular tachycardia/fibrillation was assessed in a Langendorff system. Fast Fourier transforms were applied on the recorded ventricular tachycardia/fibrillations. Training reduces low to high frequency ratio of heart rate variability at week 8 compared with that at week 1 ( P <0.05). In isolated hearts, the probability for ventricular tachycardia/fibrillation was decreased from 4.5±0.8% in sedentary controls to 1.56±0.2% in intensive training controls ( P <0.05) and from 13.5±2.1% in the sedentary group to 5.4±1.2% in the intensive training group ( P <0.01). Moreover, the pacing current required for ventricular fibrillation induction in the trained groups was increased following exercise ( P <0.05). Fast Fourier transform analysis of ECG findings revealed an exercise‐induced ventricular fibrillation transition from a narrow, single‐peak spectrum at 17 Hz in sedentary controls to a broader range of peaks ranging from 13 to 22 Hz in the intensive training controls. Conclusions: Intensive exercise in infarcted rats leads to reduced ventricular fibrillation propensity and is associated with normalization of refractoriness and intrinsic spatiotemporal electrical variations.